Effects of Cold Surface Temperature on Frosting Characteristics and Anti-Frosting Performance of Superhydrophobic Fins - Wang Feng; Tang Rui; Wang Zhihao; Yang Weibo; Gao Ang (Zhileng xuebao)
To determine the influence of cold surface temperatures on the frosting characteristics and anti-frosting performance of superhydrophobic fins, the frosting process on superhydrophobic fins under different cold surface temperatures was studied. A visual frosting experimental system was built and the results were compared with those of bare fins without surface treatment. As the cold surface temperature decreased, the onset freezing time of condensate droplets, half freezing time, and complete freezing time on the superhydrophobic fin surface were shortened. The lower the cold surface temperature, the smaller the critical radius of the crystal nucleus, the denser the crystal nucleus, and the higher the surface coverage when the droplets were completely frozen. The frost thickness of the superhydrophobic and bare fins increased as the cold surface temperature decreased. After frosting for 45 min, the frost thickness on the superhydrophobic fins at cold surface temperatures of ?5, ?10, ?15, and ?20 °C were 78.8%, 95.6%, 94.6%, and 78.8% of those on bare fins, respectively. This indicates that superhydrophobic fins have an anti-frosting effect at different cold surface temperatures.